Afforestation with Broom as a Nurse Crop - Chinnamani, S.; Gupte, S. C.; Rege, N. D.; Thomas, P. K. (Indian Forester, 1965)
Existing dense natural growth of broom and gorse, the exotic leguminous shrubs has been successfully utilised as a nurse crop for afforesting bluegum and black wattle. The afforestation has heen successfully done in 3’ (0.9 m ) wide lines 11’ (3.4 m) part. 1 foot cube (0.09 m ) pits were dug at 11’ Ã— 10’ espacement and mossed seedlings were planted. The dense broom afforded protection to the seedlings against frost, wind, etc. The growth was better under broom than in the open. The broom growth was removed during the middle of the second year. During the fourth year broom formed a dense undergrowth due to the growth of coppice shoots and natural regeneration by seed. This method is 30 to 40% cheaper than the conventional clearing and afforestation of such areas. it also minimised erosion hazards .